178 RANDOMIZED CONTROLLED TRIAL COMPARING ANGLE OF HIS ACCENTUATION WITH TOUPET FUNDOPLICATION IN PATIENTS UNDERGOING LAPAROSCOPIC HELLERS MYOTOMY: INTERIM RESULTS. (17th September 2021) - Parshad, Rajinder; Bale, Manjunath; Bhattacharjee, Hemanga; Singla, Vitish; Saraya, Anoop; Sharma, Raju
Abstract:  : Laparoscopic Heller's Cardiomyotomy (LHCM) is the surgical treatment of choice for achalasia. Addition of an antireflux procedure is recommended to reduce the postoperative reflux. However, there is no consensus regarding the ideal antireflux procedure. In an earlier study we have shown that Angle of His accentuation (AOH) is similar to Dor fundoplication. In this study we present the interim results of an RCT comparing AOH with Toupet fundoplication as an adjunct to LHCM. Methods: Patients of Achalasia cardia presenting after October 2017 were randomised to receive either AOH or Toupet following Heller cardiomyotomy based on computer generated random sequence. Primary outcome was incidence of post-operative symptomatic reflux and esophagitis on endoscopy. Secondary outcome was relief of dysphagia and Achalasia specific health related Quality of life assessment (ASHRQoL). Symptom scores for dysphagia, regurgitation and heartburn as well as ASHRQoL were noted pre operatively and at 3 monthly intervals. Objective evaluation was done using timed barium swallow, Upper GI endoscopy and oesophageal manometry. Data was recorded on excel spreadsheet and analysis done using SPSS v5. Results: A total of 52 patients (25 Toupet, 27 AOH) were included in the analysis. All patients were successfully operated laparoscopically with no conversions, intraoperative perforations or perioperative mortality. The mean operative duration was 128 min in the AOH group and 146 min in the Toupet group (p < 0.05). There was significant improvement in symptom scores as well as objective parameters in both groups with no difference between the 2 groups at a mean follow-up of 6 months (5-9 months; Table 1). 3 patients in AOH group (11%) and 4(16%) patients had new onset reflux with esophagitis in 2 patients in each group. Conclusion: AOH is technically easier and can be performed in a shorter time. The symptom relief is similar in both groups with similar incidence of heartburn and esophagitis in the short term. A longer follow up is recommended in a larger number of patients.